Efisiensi Produksi melalui Otomatisasi Sederhana Pada Industri Kerajinan Skala Rumah - Fahmi, Ijal; Rusmina, Cut, Nelly, Maryam; Mustafa, Reza (Jurnal Serambi Engineering, 2025)
This study aims to analyze the implementation of simple automation as a strategy to enhance production efficiency in small-scale home craft industries. In an increasingly competitive creative economy, small business owners are required to improve productivity without investing heavily in advanced technology. This research employs a descriptive qualitative approach using the Systematic Literature Review (SLR) method to identify relevant forms of simple automation, including semi-mechanical tools, time-based work systems, and ergonomic production layouts. The results indicate that simple automation can increase work efficiency, reduce human error rates, and lower production costs by approximately 25-40% without compromising product quality. Furthermore, the adoption of simple automated systems positively impacts production stability and competitiveness in household craft enterprises. This study contributes to practical insights for micro and small entrepreneurs as well as policymakers in developing sustainable efficiency strategies through affordable and context-appropriate technological innovation